2020
DOI: 10.1002/adsc.202000736
|View full text |Cite
|
Sign up to set email alerts
|

A Decarboxylative C(sp3)−N Bond Forming Reaction to Construct 4‐Imidazolidinones via Post‐Ugi Cascade Sequence in One Pot

Abstract: A post-Ugi one-pot cascade was developed to access 4-imidazolidinones through an intramolecular decarboxylative C(sp 3)À N bond forming reaction. The reaction has a broad tolerance for a variety of substituted aldehydes, anilines, isocyanides and glyoxylic acids. The cascade reaction scope was expanded to synthesize spiroimidazolidinone by the replacement of aldehyde with aliphatic ketone in the Ugi reaction. Subsequently, the methodology was applied to synthesize the core structures of pharmaceuticals GSK2137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…, Me, MeO, t -Bu) could be tolerated well, and afforded yields from 79% to 83% ((±) 5g–i). These results were consistent with data from our previous work 16,17 and suggested that the nucleophilic attack occurred between the carbanion and ketone of benzoylformic acid. For the isocyanide moiety, commercially available 4-methoxyl benzyl isocyanide was investigated to broaden the substrate scope and evaluate reaction compatibility.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…, Me, MeO, t -Bu) could be tolerated well, and afforded yields from 79% to 83% ((±) 5g–i). These results were consistent with data from our previous work 16,17 and suggested that the nucleophilic attack occurred between the carbanion and ketone of benzoylformic acid. For the isocyanide moiety, commercially available 4-methoxyl benzyl isocyanide was investigated to broaden the substrate scope and evaluate reaction compatibility.…”
supporting
confidence: 93%
“…Hence, we analysed the sequence mechanism employed to construct pyrrolopyridinones, indoline-piperidinones and 4-imidazolidinones by our research team. 16 Ugi adducts were formed using a mixture of benzoylformic acid, ethyl glyoxylate, isocyanide and an aromatic amine (containing an electron-withdrawing group). We postulated that, in this Ugi core, the reaction started with nucleophilic attack of a carbanion to afford the four-membered azetidin-2-one ring ( Scheme 2 , path A).…”
mentioning
confidence: 99%
“…A series of 4-imidazolidinone derivatives exhibited modest anticancer cytotoxicity against a variety of cancer cell lines [23]. With the aim of searching for more 4-imidazolidinone compounds with anticancer activity, we synthesized a batch of compounds with a 4-imidazolidinone motif consistent with the previous description [14] and evaluated their anticancer effect in cultured human cancer cells. We also explored the molecular mechanism of anticancer activity of compound 9r, which harbored the best anticancer effect among these compounds in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we synthesized a small library of 4-imidazolidinones (Scheme 1) [14]. To evaluate the anticancer activity of compounds 9, we first examined the tumor cell growth inhibition activity in human cancer cell lines.…”
Section: Anticancer Activity Evaluation Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation